2019
DOI: 10.1103/physreve.100.040301
|View full text |Cite
|
Sign up to set email alerts
|

Reentrant phase transitions in threshold driven contagion on multiplex networks

Abstract: Models of threshold driven contagion explain the cascading spread of information, behavior, systemic risk, and epidemics on social, financial and biological networks. At odds with empirical observation, these models predict that single-layer unweighted networks become resistant to global cascades after reaching sufficient connectivity. We investigate threshold driven contagion on weight heterogeneous multiplex networks and show that they can remain susceptible to global cascades at any level of connectivity, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This transition is determined by β j dt, the probability of an uninfected neighbour in configuration j becoming infected over an interval dt (see Methods for an explicit calculation). Taken together, W ego and W neigh accurately describe diffusion dynamics over static networks with heterogeneous edge types, such as weighted and multiplex networks 33,34 .…”
Section: Master Equation Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This transition is determined by β j dt, the probability of an uninfected neighbour in configuration j becoming infected over an interval dt (see Methods for an explicit calculation). Taken together, W ego and W neigh accurately describe diffusion dynamics over static networks with heterogeneous edge types, such as weighted and multiplex networks 33,34 .…”
Section: Master Equation Solutionmentioning
confidence: 99%
“…Threshold dynamics, also known as complex contagion, are used to model the spread of information where infection requires the reinforced influence of at least a certain fraction of neighbours in the egocentric network 29 . Thresholddriven dynamics over static networks have been extensively studied both empirically 30 and theoretically [30][31][32][33][34] , but analysis of their behaviour on temporal networks is so far limited to a small number of empirical studies [35][36][37][38] . Using random reference models of temporal networks, it has been shown that when infection is driven by the fraction of infected neighbours, rather than their absolute number, bursty interactions may lead to deceleration 35,36,38 .…”
mentioning
confidence: 99%
“…For example, some studies have shown that a global cascade can occur more easily when a network is highly clustered [8][9][10] or is positively degree-correlated [11][12][13][14] than when it is not. Other studies have investigated the Watts model on modular networks [11,[15][16][17], temporal networks [18][19][20], and multiplex networks [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Threshold dynamics, also known as complex contagion, are used to model the spread of information where infection requires the reinforced influence of at least a certain fraction of neighbours in the network [28]. Threshold * samuel.unicomb@gmail.com driven dynamics over static networks have been extensively studied both empirically [29] and theoretically [29][30][31][32][33], but analysis of their behaviour on temporal networks has been limited to a small number of empirical studies [34][35][36][37]. Here we propose an analytical framework to systematically describe the relationship between the diffusion of information and bursty temporal interactions, thus providing the theoretical foundation necessary to uncover the role of burstiness in generic diffusion processes, including simple and complex contagion models of physical, biological and social phenomena.…”
mentioning
confidence: 99%
“…This transition is determined by β j dt, the probability of an uninfected neighbour in configuration j becoming infected over an interval dt (see Methods for an explicit calculation). Taken together, W ego and W neigh accurately describe diffusion dynamics over static and heterogeneously distributed edges, such as weighted and multiplex networks [32,33].…”
mentioning
confidence: 99%